Pengaruh Pertumbuhan Perusahaan Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi Pada Perusahaan Maufaktur Sektor Energi Yang Terdaftar Di BEI Tahun 2020-2024 - Dwi Suci Ramadhani; Elfiswandi .; Putri Intan Permata Sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of company growth and managerial ownership on firm value with capital structure as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2024. The population in this study consists of energy sector companies listed on the Indonesia Stock Exchange during 2020-2024, totaling 91 companies. The research sample includes 24 companies over 5 years, resulting in a total of 120 company data points, using purposive sampling method. The data in this study are secondary data in the form of annual data obtained from the official Indonesia Stock Exchange website and the official websites of the respective companies. The data analysis methods used in this study include descriptive statistical tests, classical assumption tests, panel data regression analysis, and hypothesis testing using E-Views 10. The research results indicate that: a) Company growth does not have a significant effect on firm value, b) managerial ownership has a significant effect on firm value, c) capital structure is able to moderate and strengthen the effect of company growth on firm value but is not significant, d) capital structure is unable to moderate and weakens the effect of managerial ownership on firm value but is significant. Suggestions for future research include extending the observation period so that the research results will be much more representative, as well as adding research variables to strengthen the research findings.